Situational analysis on safety and health in primary school in Kota Bharu - Nurul AH,; Tengku MA, (Department Of Community Health, Faculty of Medicine, Universiti Kebangsaan Malaysia, 2009)
Background : Safety and health is one of major concerns in public health issues. There are lots of injuries or accidents reported in the news which include school accidents and injuries. Methodology : This survey was conducted among head of primary schools in Kota Bharu from May to June 2004. The objective of this study was to investigate the awareness about safety and health status among school’s head using a questionnaire. Result : The study showed that knowledge on safety and health among the school’s heads were relatively low (7.7%). Forty-two percent of the schools did not implement any safety and health programme while more than 50 % did not have safety policies in their school. Conclusions : It is necessary to have specific safety programmes in school in order to improve the safety and health awareness among teachers, staff, students and community.